The Returns to Cognitive Abilities and Personality Traits in Germany - Guido Heineck; Silke Anger (Labour Economics, 2010)
We provide the first joint evidence on the relationship between individuals' cognitive abilities, their personality and earnings for Germany. Using data from the German Socio-Economic Panel Study, we employ scores from an ultra-short IQ-test and a set of measures of personality traits, namely locus of control, reciprocity and all basic items from the Five Factor Personality Inventory. Our estimates suggest a positive effect of so-called fluid intelligence or speed of cognition on males' wages only. Findings for personality traits are more heterogeneous. However, there is a robust wage penalty for an external locus of control for both men and women.
Additional information: NOTICE: This is the author's version of a work that was accepted for publication in Labour Economics. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Labour Economics 17 (2010), 3, pp. 535-546 and is online available at http://dx.doi.org/10.1016/j.labeco.2009.06.001.
Keywords: J24; J31; I21; 330; Cognitive abilities; Personality traits; Five Factor Model; Locus of control; Reciprocity; Wages; Lohnniveau; Persönlichkeitspsychologie; Panel; Deutschland